Implementasi Sumber Belajar Bioteknologi Berbasis Etnosains di Madrasah Ibtidaiyah Al-Munawaroh - Forniawan, Ary (Al Jahiz, 2022)
Research objectives to determine the application of ethnoscience based biotechnology learning resources in learning and describes the implementation of the ethnoscience-based biotechnology learning process. The research method uses a qualitative descriptive research design. Subjects were 49 students of class VI Madrasah Ibtidaiyah Al-Munawaroh research object of ethnoscience-based biotechnology learning resources. data collection techniques with interviews and observation. Data analysis techniques with data collection, reduction, presentation, and conclusions. The results of data analysis showed that 49.8% of students did not understand the concept of biotechnology, the manufacturing process, the microorganisms involved, the mechanism of the fermentation process in tempe, peuyeum and bread. 100% of students know tempe, peuyeum, bread and tempe is consumed every day and the way of making it was handed down by our ancestors from generation to generation. 73% of students have not been able to provide examples of other biotechnology products and the microorganisms that play a role. Conclusion Madrasah Ibtidaiyah Al-Munawaroh has implemented ethnoscience-based biotechnology learning resources in learning but the implementation of students' ethno-science-based biotechnology learning processes is unable to explain the link between local wisdom culture and natural science.